American cinema of the 2000s : themes and variations - Corrigan, Timothy, 1951- (Screen decades., 2012)
The decade from 2000 to 2009 is framed, at one end, by the traumatic catastrophe of the 9/11 attacks on the World Trade Center and, at the other, by the election of the first African-American president of the United States. In between, the U.S. and the world witnessed the rapid expansion of new media and the Internet, such natural disasters as Hurricane Katrina, uprisings around the world, and a massive meltdown of world economies. In American Cinema of the 2000s, essays from ten top film scholars examine such popular series as the groundbreaking Matrix films and the gripping adventures of for.